Dynamic equilibrium of displacement damage defects in heavy-ion irradiated tungsten. (1st January 2023) - Wang, Shiwei; Guo, Wangguo; Schwarz-Selinger, Thomas; Yuan, Yue; Ge, Lin; Cheng, Long; Zhang, Xiaona; Cao, Xingzhong; Fu, Engang; Lu, Guang-Hong
Abstract: How displacement damage defects generate and evolve in materials irradiated by energetic particles is a perennial topic in the field of nuclear materials. Here we experimentally reveal the dynamic equilibrium of displacement damage defects at room temperature and their subsequent influence on deuterium retention in tungsten. As irradiation dose increases, the major interstitial-type defects transform from dislocation loops (≤ 0.1 dpa) to dislocation lines (0.1–0.15 dpa) and then to dislocation networks (≥ 0.15 dpa), and finally the dynamic equilibrium of defects featured by a stable microstructural configuration of the coexistence of networks and loops is reached (≥ 0.2 dpa). In contrast, no significant changes in the dominant category of vacancy-type defects are observed above 0.05 dpa due to the higher migration barriers of vacancy clusters than interstitial clusters at room temperature. The defect dynamic equilibrium is confirmed via multiple results: the damage microstructure asymptoticly reaches a steady-state expressed by a constant density and size of defects, the hardness does not increase anymore, and the deuterium retention saturates. The nature of defect dynamic equilibrium is that the generation and annihilation of radiation defects restrict each other so that total defect content approaches an approximate constant under continual irradiation. Besides, we also verified the saturation of deuterium retention is inseparable from the defect dynamic equilibrium in a highly irradiated tungsten. These findings will convey some fresh insights into defect evolution and fuel inventory in tungsten and even other materials in the limit of high doses. Graphical abstract: Image, graphical abstract